PENERAPAN METODE SIMULASI ROLE PLAY UNTUK MENINGKATKAN MAHARATUL QIRA’AH SISWA KELAS V MI MASYARIQUL ANWAR BANDAR LAMPUNG - Ratih Kurnia; Zulhanan Zulhanan; Asti Fauziah (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
ABSTRACT This study was motivated by the low level of maharatul qira’ah (Arabic reading skills) among students without a boarding school (pesantren) educational background, which often leads to difficulties in understanding Arabic language learning materials. This condition is further exacerbated by students’ low learning motivation, the limited availability of qualified Arabic language teachers, and the use of less varied instructional methods. The purpose of this study was to improve the maharatul qira’ah skills of fifth-grade students at MI Masyariqul Anwar Bandar Lampung through the implementation of the role-play simulation method. This study employed a Classroom Action Research (CAR) design conducted in two cycles, with each cycle consisting of two meetings. Data were collected through observation, interviews, tests, and documentation and were analyzed using qualitative and quantitative approaches. The findings revealed that the implementation of the role-play simulation method, combined with reading activities, discussions, and supporting instructional media, enhanced students’ participation, self-confidence, and reading skills. Quantitatively, the percentage of learning mastery increased from 20% in the pre-cycle stage to 53% in Cycle I and reached 93% in Cycle II. This 73% improvement indicates that the role-play simulation method is effective in developing students’ maharatul qira’ah skills. Furthermore, the findings provide a practical contribution to the development of Arabic language instruction at the Islamic elementary school level by promoting a more active, engaging, and student-centered reading learning process. ABSTRAK Penelitian ini dilatarbelakangi oleh rendahnya kemampuan maharatul qira’ah siswa yang tidak memiliki latar belakang pendidikan pondok pesantren, sehingga mengalami kesulitan dalam memahami pembelajaran bahasa Arab. Kondisi tersebut diperparah oleh rendahnya minat belajar siswa, keterbatasan tenaga pendidik bahasa Arab, serta penggunaan metode pembelajaran yang kurang variatif. Penelitian ini bertujuan untuk meningkatkan kemampuan maharatul qira’ah siswa kelas V MI Masyariqul Anwar Bandar Lampung melalui penerapan metode simulasi role play. Penelitian menggunakan desain Penelitian Tindakan Kelas (PTK) yang dilaksanakan dalam dua siklus, dengan setiap siklus terdiri atas dua pertemuan. Teknik pengumpulan data meliputi observasi, wawancara, tes, dan dokumentasi, sedangkan data dianalisis secara kualitatif dan kuantitatif. Hasil penelitian menunjukkan bahwa penerapan metode simulasi role play yang dipadukan dengan aktivitas membaca, diskusi, dan penggunaan media pendukung mampu meningkatkan partisipasi, kepercayaan diri, serta kemampuan membaca siswa. Secara kuantitatif, persentase ketuntasan belajar meningkat dari 20% pada pra-siklus menjadi 53% pada siklus I dan mencapai 93% pada siklus II. Peningkatan sebesar 73% tersebut menunjukkan bahwa metode simulasi role play efektif dalam mengembangkan kemampuan maharatul qira’ah siswa. Temuan ini memberikan kontribusi praktis terhadap pengembangan pembelajaran bahasa Arab di tingkat madrasah ibtidaiyah, khususnya dalam menciptakan proses pembelajaran membaca yang lebih aktif, menarik, dan berpusat pada siswa.